Análisis para la implementación de un sistema de gestión de incidencias en el ISP Bawebdi del Cantón Pueblo viejo. - Barco Monserrate, Washington Javier (2023)
An incident management system allows to organize and manage customer information and events, however, the company ISP Bawebdi has problems in the control, allocation and resolution of these incidents, affecting the quality and performance of the service offered by this internet provider. The objective of this research was to analyze the implementation of an incident management system to improve the quality of the Internet service offered by ISP BAWEBDI in the canton of Pueblo Viejo. For this purpose, we used a methodological planning with descriptive and exploratory research that allowed us to observe and analyze the events and inconveniences, as well as their cataloguing. The deductive and inductive methods were relevant for the development of the project since they allowed us to relate different points of view through the collection of information. It was possible to determine the needs and requirements of the company, where it was possible to contrast that the implementation of the incident system will be convenient because it will allow to increase the response time to incidents, as well as its prioritization of incidents, allowing to satisfy the needs and requests of the client. The Incident Management System project at Bawebdi ISP in Puebloviejo Canton seeks to improve the customer experience by providing an efficient platform for managing technical problems and service requests. This will result in increased customer satisfaction and a more efficient operation on the part of the ISP.